SOURCES OF PUPILS DECISION MAKING ABOUT TECHNOLOGY - ZUBATA, Anna; PLISCHKE, Jitka; KROPAC, Jiri (Trends in education, 2014)
This article deals with decisions, interests, experiences, self-efficacy and their potential interdependencies in the context of technology. In the introductory part of the article there is a definition of terms above mentioned. The conclusion of the article there is the research, which deals with the aforementioned dependencies.
Keywords: Decision making; interests; self-efficacy; experience; technology.